2013
DOI: 10.1002/hyp.9797
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐ and post‐impoundment nitrogen in the lower Missouri River

Abstract: Abstract:Large water-sample sets collected from 1899 through 1902, 1907, and in the early 1950s allow comparisons of pre-impoundment and post-impoundment (1969 through 2008) nitrogen concentrations in the lower Missouri River. Although urban wastes were not large enough to detectably increase annual loads of total nitrogen at the beginning of the 20 th century, carcass waste, stock-yard manure, and untreated human wastes measurably increased ammonia and organic-nitrogen concentrations during low flows. Averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…For example, from 1996 to 2008, over 2400 wetlands were created in Sweden with support from different national programs, with the aim of remediating runoff from agriculture and decreasing N transport to the eutrophicated Baltic Sea [5]. In the US, the ongoing restoration and creation of wetlands along the Missouri River is part of a strategy to decrease N loads to the Mississippi River and eventually, to the Gulf of Mexico [6]. In Ireland, the Integrated Constructed Wetland concept has been used to address the pressure from different EU directives to improve water quality at the landscape scale since 2007 [7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, from 1996 to 2008, over 2400 wetlands were created in Sweden with support from different national programs, with the aim of remediating runoff from agriculture and decreasing N transport to the eutrophicated Baltic Sea [5]. In the US, the ongoing restoration and creation of wetlands along the Missouri River is part of a strategy to decrease N loads to the Mississippi River and eventually, to the Gulf of Mexico [6]. In Ireland, the Integrated Constructed Wetland concept has been used to address the pressure from different EU directives to improve water quality at the landscape scale since 2007 [7].…”
Section: Introductionmentioning
confidence: 99%
“…This could be a function of location because Hermann is located downstream of two major tributaries (Gasconade and Moreau rivers) that drain watersheds with relatively little agricultural activity and another major tributary (Osage River) with multiple reservoirs resulting in a potential dilution effect. Blevins et al [24] suggested that total organic nitrogen and TN loadings between St. Joseph, MO and Hermann, MO experienced a dilution effect. Despite few significant differences in TN and NO 3 -NO 2 concentrations, visual comparisons of box plots showed that median elutriate concentrations at Benedictine, Bakers and Jameson were often located near the upper range of concentrations sampled at our monitoring stations, which suggests that an increase in TN and NO 3 -NO 2 concentrations in the Missouri River during chute construction may occur; however, the range of elutriate concentrations for these proposed construction sites still overlapped considerably with the range of monitoring station concentrations, especially for TN.…”
Section: Discussionmentioning
confidence: 99%
“…The urban areas and municipal waste can also provide a significant source of nitrate to the water system. For example, the growth rate of nitrate concentration in the Mississippi River was between 5% and 13% due to urbanization between 2000 and 2008 [10]. Approximately 64% of the nitrate in the water systems of Slovenia came from domestic wastewater and the agricultural sector [11].…”
Section: Introductionmentioning
confidence: 99%